Effect of martensite volume fraction on mechanical properties of dual-phase treated AISI-4012 sheet steels - Aksakal, B.; Karaca, F.; Arikan, R. (Carl Hanser Verlag, 2010)
Hot rolled AISI-4012 sheet steels have been heat treated to obtain a ductile dual phase microstructure. The specimens were heat treated in the ferrite (a) and austenite (7) phase region at temperatures of 740, 760, 790 and 820 degrees C and corresponding time intervals of 15, 30, 60 and 90 min and then quenched into water. Hardness measurements, tensile, bending, and impact tests were performed in order to determine the mechanical properties of the dual phase steel. These were examined with respect to the martensite volume fraction. Both the flow and tensile stresses increased whereas elongation decreased with increasing dual phase treatment temperature and martensite volume fraction. The optimum mechanical properties and the appropriate dual-phase microstructure are achieved at 740 and 760 degrees C annealing with subsequent water quenching. From examinations it was deduced that ductile fracture occurred in the tested samples.
Keywords: Hot rolled sheets; Dual phase; Microstructure; Mechanical properties